CHRONIC SMOKING AND PORNOGRAPHIC ADDICTION IN SCHIZOPHRENIA PATIENT WITH URBAN LIVING: CASE REPORT - Gumilar Fardhani Ami Putra; Zain Budi Syulthoni; Zuhrotun Ulya (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Introduction – Urban living, chronic smoking is a risk factor in schizophrenia. Pornographic addiction is also a potential risk factor of schizophrenia considering its neurobiological pathways. Schizophrenia is one of the most dangerous mental illness contributing to 2,8% years lived with disability. Considering many people with urban living, chronic smoking, and pornographic consumption, relation of these risk factors to schizophrenia is demonstrated in this case report. Methods – Presented the case of the patient, 39 years old with psychotic symptoms was found to be born and lived most of his life in urban area, smoking since junior high school, and often consumed pornographic contents since senior high school. Data were taken from psychiatric interviews, general, and mental status examinations in psychiatric clinics, then a literature review was carried out. Results – People who born, and live through their live longer in a larger city, have more risk of Schizophrenia. Patient was known to be born in one of the biggest city in Indonesia, before moved out to another urban area in different countries in last two years. Crave with chronic smoking and pornographic addiction become one of contraproductive conduct source which arise difficulty in patient’s side to take an health life style with the risk of poor prognosis and mental health deterioration. Discuss – People who born and live longer in urban areas such as cities are in increased risk of schizophrenia due to social status awareness and fast paced life induce brain stress. Chronic smoking is a risk factor of schizophrenia due to the effect of nicotine on dopamine levels. Pornographic addiction is a potential risk factor due to addiction pathway effect on dopamine threshold. Conclusion – Urban living, chronic smoking, and pornographic addiction are risk factors associated with schizophrenia found in this case report. Epidemiologic and pathophysiological mechanisms behind these risk factors are an interesting view for physician dealing with schizophrenia patients. Awareness of social status and fast paced life in urban lifestyle, pathways of nicotine in dopamine dysregulation, and dopamine-related impairment in addiction are the neurobiological mechanisms behind these risk factors which a physician needs to be aware of. Keywords: schizophrenia, urban living, chronic smoking, pornographic addiction